Cities in Crisis: Exploring Discontents and Challenges of Unplanned Urban Growth in Bangladesh - Buddha Dev Biswas; Shaira Matin (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2025)
Urbanization has accelerated rapidly over the past few decades in all divisional cities of Bangladesh. This paper closely examines the nature and extent of urbanization in Bangladesh, particularly in Dhaka and Chittagong the two mega cities of the country. It provides a historical analysis of migration patterns, changes in population structure, and the pressure on infrastructure, health facilities, education, electricity supply, safe drinking water in urban centres, with a special focus on the expanding slum sector. Qualitative data analysis on the scale of migration is used to model the stakes in social systems and urban architecture. A primary analysis of infrastructure deficits in transportation, housing, and public services assesses the system’s limited capacity to meet current urban demands. To gauge the depth of urban discontent, sanitation, lighting, and access to food, water, and clothing in slum areas are also examined. Inspired by Ananya Roy’s work, the study uses subaltern urbanism to highlight informal settlements not as urban failures rather as an alternative urban development through innovation, resistance and alternative forms of urban modernity. Finally, policy debates and urban planning prescriptions are presented to address these challenges, aiming to enhance Bangladesh's future urban development by reducing vulnerability and promoting inclusive growth. This paper contributes to the literature on sustainable urban development in rapidly developing regions.